Trend Topics in Local Government Financial Reporting in Emerging Digital Technology: A Bibliometric Analysis - Revina Aulia; Muhammad Din; Femilia Zahra; Masruddin Masruddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The purpose of this article is to identify and discuss the dynamics and trends in the literature on financial reporting in local government and in the era of digital development by conducting descriptive analysis. The analysis network encompasses conceptual, intellectual, and social structures that impact the development of future research agendas. The study utilised bibliometric analysis using the Biblioshiny tool from RStudio. We analysed 566 documents from the Scopus database covering the period from 1970 to 2025. The findings of this study emphasise that the use of technologies such as blockchain, artificial intelligence, big data analytics, and IoT as tools to address and control environmental issues assists with internal control processes in local government and community-government relations by contributing to community participation in local government decision-making. Finally, it assists with administrative processes within organisations. This study suggests that organisations must adopt technological developments such as blockchain, artificial intelligence, big data analytics, and IoT. The competencies of civil service accountants must be dynamic and adaptive to keep pace with changing times and environmental uncertainty. Ultimately, university curricula should be updated to reflect the current use of technology. This study contributes to the literature on local government financial reporting in the era of digital development by providing a global overview of the impact of technological developments, skills, and the accounting profession, thereby identifying gaps that will influence future research agendas.